Efektifitas Tematik terhadap Kerja Kelompok Kelas II SD Negeri Genengmulyo 02 Kecamatan Juwana Kabupaten Pati - Kundono Kundono; Nur Fajrie; Sri Surachmi W (Journal on Education, 2023)
The low use of learning models that are not varied and teachers tend to use conventional models. This research was conducted at SDN Genengmulyo 02, Juwana District, Pati Regency. Principals and homeroom teachers for Grade 2 and the learning outcomes of grade 2 students at SDN Genengmulyo 02 became the object of research. The purpose of this study was to apply the group work method to an energy source and examine whether its use improves learning performance in grade 2 students of Pati Regency, Juwana District, SDN Genengmulyo 02. The group work method can be interpreted as a teaching and learning format that focuses on the interaction between members with one another in a group, in order to complete learning tasks together. After the research was conducted, it was concluded that the selection of appropriate learning methods and models could improve student achievement outcomes. Based on the research findings, Class II teachers are encouraged to further develop relevant learning models regarding energy sources and their use